2015
DOI: 10.1016/j.bbr.2015.05.055
|View full text |Cite
|
Sign up to set email alerts
|

Binge alcohol drinking elicits persistent negative affect in mice

Abstract: Cessation from chronic alcohol abuse often produces a dysphoric state that can persist into protracted withdrawal. This dysphoric state is theorized to function as a negative reinforcer that maintains excessive alcohol consumption and/or precipitates relapse in those struggling to abstain from alcohol. However, we know relatively little regarding the impact of cessation from binge drinking on behavioral measures of negative affect and related neurobiology. Male C57BL/6J mice were given access to unsweetened 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

27
163
9

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 90 publications
(199 citation statements)
references
References 85 publications
(85 reference statements)
27
163
9
Order By: Relevance
“…When assayed at 24 h withdrawal, the adult bingers in this study exhibited hyper-anxiety in the marble burying test, which is consistent with our previous data showing an increase in marble burying in adult mice with a 30-day history of binge drinking (Lee et al, 2015). This suggests that even a relatively brief, 2-week period, of binge-drinking is sufficient to elicit a negative affective state in adult animals.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…When assayed at 24 h withdrawal, the adult bingers in this study exhibited hyper-anxiety in the marble burying test, which is consistent with our previous data showing an increase in marble burying in adult mice with a 30-day history of binge drinking (Lee et al, 2015). This suggests that even a relatively brief, 2-week period, of binge-drinking is sufficient to elicit a negative affective state in adult animals.…”
Section: Discussionsupporting
confidence: 92%
“…However, consistent with our previous study in adults (Lee et al, 2015), all binging animals, irrespective of age, exhibited hyper-activity in the FST, as evidenced by reduced time spent immobile and a lower number of immobile episodes, relative to water controls. Although the FST is typically used as an assay of depression, based on increased floating behavior (Porsolt et al, 2001), we have reliably observed a decrease in floating behavior in animals with a history of binge-drinking.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations